Improving the Seventh Grade Students’ Reading Comprehension Achievement by using Numbered Heads Together Technique at Patsan Witaya Muliniti School - Malee, Husna; Rofiq, Annur; Sukmaantara, I Putu (EFL Education Journal, 2022)
The objective of this research was to improve the junior high school students' reading comprehension by using Number Head Together technique at Patsan Witaya Mulinti School. The design of this research was Classroom Action Research. Patan Wittaya foundation school was chosen purposively as the research area because the students on this school still had difficulties in learning reading comprehension. Based on the observation, the findings showed that the students who could fulfil the indicators on the observation checklist of the active therefore participation increased from 25 (78.12 %) students in Meeting 1 to 26 (84.37%) students in Meeting 2 because some students were having difficulties in understanding the reading text. Meanwhile, the reading comprehension test results in Cycle 1 fulfilled the research’s target score. Based on the findings, it can be seen that students’ average score in the reading comprehension was 83.96. After conducting the actions, the results of this current study indicated that Numbered Heads Together technique is an effective technique to improve the students’ active participation and reading comprehension achievement. It could be concluded that the use of the number heads technique could improve the junior high school students' reading comprehension.